Association between dental agenesis and facial morphology. A cross-sectional study in France. - Damien Brézulier; Pierre Raimbault; Sylvie Jeanne; Tiphaine Davit-Béal; Guy Cathelineau (PLoS ONE)
Purpose Knowing the features of dental evolution and facial morphology, marked by an increase in the prevalence of agenesis and a tendency towards verticalization of the face, the main objective of this cross-sectional observational study was to assess the correlation between the occurrence of agenesis (of 3rd molars or other teeth) and facial morphology in the French population. Methods The study was conducted at the University Hospital of Rennes, France, from June 2022 to October 2022. Patients aged 12-18 years who underwent a global orthodontic assessment were included. Data collected from medical examinations, panoramic, anteroposterior, and lateral x-rays were analyzed for cephalometric and dental features. The association between morphological parameters and agenesis of wisdom teeth or other teeth was assessed by univariate and multivariate analysis. Results The study included 259 patients, of whom 89 presented agenesis. Logistic regression analyses identified several morphological parameters associated with agenesis. In the multivariate model, a negative correlation was found between tooth agenesis and FMA (OR = 0.85; p < 0. 001), facial axis (OR = 0.92; p = 0.040), and a positive one with SNB (OR = 1.17; p = 0.023), ANS-Xi-Pm (OR = 1.12; p = 0.013). Conclusion This study highlights the correlation between agenesis occurrence and specific cephalometric parameters in the French population. The findings suggest that transverse constriction of the maxilla, facial divergence, and anterior projection of the chin symphysis are associated with agenesis. Trial registration number: Opinion n°22.103, dated 06.04.2022.